ANALISIS PENGARUH LDR, BOPO, NIM DAN NPL TERHADAP RETURN OF ASSET PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 - 2020 - Melly Yulianti (Akuntansi Prima, 2022)
Abstract Return on Assets (ROA), Non Performing Loans (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio. Banks play an important role as financial intermediaries between needy parties. Banking is an institution that plays an important role in the distribution of funds for business units that have more financial conditions (surplus) with those of business units with less financial conditions (deficit).